Can Halal Tourism in Lombok be Sustainable? A Case Study of Stakeholder Perspective - Puput Yanita Senja; Wahyu Dian Silviani; Syed Muhammad Abdul Rehman Shah (Journal of Islamic Economic and Business Research, 2024)
This study explores the potential of Indonesia, particularly Lombok, as a leading halal tourism destination. Despite being ranked first in the Global Muslim Travel Index (GMTI) by 2023, Indonesia has yet to meet its target of attracting 25% of foreign tourists as Muslims by 2022. Lombok plays a key role in this vision, yet stakeholders hold divergent views on the sustainability of halal tourism there. Discussions on the business and environmental aspects of halal tourism, with respect to stakeholder synergy and innovation, are still limited. This research aims to examine how stakeholders perceive halal tourism in Lombok and the ways in which they collaborate and innovate to ensure its sustainability. A qualitative approach was employed, using a case study method. Data were collected through in-depth interviews with five purposively selected stakeholders, chosen for their significant involvement in sustaining halal tourism. The data were analysed using Atlas.ti software to ensure accurate representation. Findings reveal contrasting stakeholder views on the future of halal tourism in Lombok. While some support it for its uniqueness, others express concerns about possible restrictions and favour alternative tourism types. For sustainability, stakeholder synergy and innovation are essential. Key measures include creating direct flight routes from Muslim-majority countries, fostering local partnerships, and promoting environmental and business sustainability. Additionally, government-driven initiatives like international events and halal certification could attract more tourists, while education and training would empower local communities.